How are oil supply shocks transmitted to the U.S. economy? - Martin Geiger; Jochen Güntner (Johannes Kepler University of Linz, Department of Economics, 2019)
We investigate how oil supply shocks are transmitted to U.S. economic activity, consumer prices, and interest rates. Using a structural VAR approach with a combination of sign and zero restrictions, we distinguish between supply and demand channels in the transmission of exogenous changes in crude oil production. We find that the adverse effects of negative oil supply shocks are transmitted mainly through the demand side, as both output and interest rates react more strongly to oil supply shocks that shift the U.S. aggregate demand curve, while the supply side matters in transmitting oil supply shocks to consumer prices.
Keywords: C32; E30; Q41; Q43; 330; Business cycles; oil supply shocks; structural VAR estimation; transmission channels